Leveraging capabilities of social media marketing for business success - Sofiane Laradi; Amina Elfekair; Mahmaod Alrawad; Mujtaba Hashim; Faten Derouez (Computers in Human Behavior Reports)
Social media platforms viewed as an integrated resources in marketing capabilities, yet there is a significant shortage and fragmentation of research articulating the dimensions of social media marketing (SMM) capabilities and their influence on brand and firm performance. The aim of this study in to investigate the influence SMM capabilities on brand equity and firm performance. Using a survey method, we gathered data from 326 firm presented at four separate exhibitions in Algeria. The structural equation modeling results shows that SMM capabilities have a positive effect on brand equity and firm performance. Furthermore, the findings shown that brand equity effect firm performance and plays a complementary role between SMM capabilities and firm performance. However, SMM capabilities have been found to have no influence on brand equity furthermore, there is no moderating effect for firm size on any of the investigated relations. The findings significantly contribute the understanding of the SMM as strategic resources and dynamic capabilities, guiding community managers, content creators, and digital analysis to optimize social media platforms abilities for communication.